NUMERICAL SIMULATION OF REINFORCED CONCRETE SHEAR WALL USING 3D-NLFEA - Ainun Najib; Bambang Piscesa; Harun Alrasyid (Institut Teknologi Sepuluh Nopember, 2022)
Reinforced concrete shear walls are the main lateral load-resisting system in reinforced concrete structures. Shear walls have high stiffness when lateral load occur, especially due to earthquake loads. In the recent earthquake, the shear wall was damaged at the boundary eelment. The damage in boundary element is triggered by out of plane instability, concrete crushing, and reinforcement buckling. This study will evaluate the performance reinforcment concrete shear wall using the three-dimensional finite element method. Furthermore, the results obtained in this study will be validated firstly against the results of existing research. Based on the results of the study, the FEM validation process provides predictions that are in accordance with the experimental results regarding the hysteresis curve and the form of damage to the shear wall with an error value of 2.07% < 5%. However, the strain of shear wall elong the height of the wall has eror 26%.